Prevalence Of Anaemia and Its Socio-Demographic Determinants in Pregnant Women: A Cross-Sectional Study in Tertiary Health Care Setup in Central India - Piyusha Mahashabde; Vinod K Arora; Shireen Sharma; Ahmed Shahjada; H M Dabhi (Medsci Publications, 2014)
Background: Anaemia in pregnancy accounts for one fifth of maternal death worldwide. The association between anaemia and adverse pregnancy outcome, higher incidence of preterm & low birth weight deliveries has been demonstrated. However, nutritional anaemia in pregnancy remains one of the India's major public health problems, despite of the fact that this problem is largely preventable. Objective: To determine the prevalence of anaemia in pregnant women and to determine association of anaemia and socio-demographic factors. Methodology: A descriptive cross sectional study was conducted among pregnant women who came to outpatient unit of obstetrics and gynecology department during March- May 2013 by using pre-designed, pretested structured schedule. Written consent was taken. Hemoglobin estimation was done by Sahli's method and anaemia was graded according to WHO criteria. Statistical analysis was done using Microsoft Excel 2007 and SPSS Version 20. Result: - Overall prevalence of anaemia among the pregnant women was found to be 63%.It was seen that 23% of women were illiterate and 58.7% of them belong to upper lower class. Factors such as level of education of women, occupation, age at first pregnancy and consumption of Iron Folic Acid were found to be significantly associated with prevalence of anaemia in pregnancy. Conclusion: - A very high prevalence of anaemia in pregnancy needs mandatory regular supply of IFA tablets to adolescent and pregnant women along with correction of other nutritional deficiencies and timely intervention for reducing the burden of related diseases.